Hubungan Pengetahuan Fungsi Gigi Terhadap Status Gizi Manula Yang Kehilangan Gigi Sebagian Di Kecamatan Mamasa Sulawesi Barat - Rangga Alfriani; Quroti A’yun; Sutrisno Sutrisno (Journal of Oral Health Care, 2018)
Teeth had very important roles and functions so that someone with poor knowledge on tooth function might have poor oral health. The poor condition of the oral cavity might cause tooth loss and if not replaced with denture would disturb the functions and activities of the oral cavity, as well as influencing nutritional status. Determining the relation between knowledge on tooth function and nutritional status of elderly people with partial tooth loss in Mamasa Sub-district, West Sulawesi. This was an observational analytical study with Cross-Sectional design performed on September–November 2017. The research variables were knowledge on tooth function and nutritional status. The total sample was 64 people. Sampling used stratified random sampling technique. Data collection used questionnaire, body height measurement tool, and body weight scale. Data analysis used Kendall-Tau test. Most of the respondents’ knowledge on tooth function was high and most of the nutritional status of the elderly people were poor. The result of analysis test showed significance value of p=0,285 in male respondents and p=0,971 in female respondents (p>0,05), showing no significant relationship between knowledge on tooth function and nutritional status of elderly people with partial tooth loss. There was no relation between knowledge on tooth function and nutritional status of elderly people with partial tooth loss.